Wide-temperature ultralow-power-consumption magnetic material as well as preparation method and application thereof

Through the combination of Fe2O3, ZnO and other components and low-temperature sintering process, magnetic materials with low power loss in the range of 25℃-80℃ were prepared, which solved the problem of high power loss in the prior art and was suitable for power supplies with frequent load factor changes. equipment achieves more efficient energy utilization.

CN119153184AInactive Publication Date: 2024-12-17广东尚朋电磁科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411484223.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing wide temperature ultra-low power consumption magnetic materials still have high power loss in the range of 25℃-80℃, which cannot meet the low energy consumption needs of servers and consumer electronic switching power supplies with frequent load factor changes.

Method used

Using the combination of main components Fe2O3, ZnO and auxiliary components CaCO3, Nb2O5, Co2O3, Ta2O5, and SiO2, magnetic materials with lower power consumption are prepared through ball milling, spray drying and low-temperature sintering processes, and the grain size and oxidation degree are controlled. Reduce sintering temperature and loss factor.

Benefits of technology

A significant reduction in power loss in the range of 25℃-80℃, especially when the energy consumption is not fully loaded, it can reach up to 200mW/cm3. It is suitable for servers and consumer electronic power supplies with frequent load factor changes, improving efficiency and reducing Heat loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153184A_ABST
    Figure CN119153184A_ABST
Patent Text Reader

Abstract

The invention discloses a wide-temperature ultralow-power-consumption magnetic material and a preparation method and application thereof, and belongs to the technical field of magnetic materials, and raw materials of the wide-temperature ultralow-power-consumption magnetic material comprise main components and auxiliary components. The preparation method of the wide-temperature ultralow-power-consumption magnetic material comprises the following steps that the main body material is mixed, subjected to ball milling and then presintered, then the obtained presintered material and the auxiliary components are mixed and subjected to ball milling continuously, powder is obtained after spray drying, the obtained powder is pressed, molded and sintered, and the wide-temperature ultralow-power-consumption magnetic material is obtained. The obtained magnetic material has wide temperature range and ultra-low power consumption, is very suitable for being applied to manufacturing of power converters in servers and consumer electronics with frequently-changed load factors, and is a current core material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of magnetic materials, and in particular relates to a wide-temperature ultra-low power consumption magnetic material and a preparation method and application thereof. Background Art

[0002] In recent years, the industry has done a lot of research to obtain wide-temperature ultra-low power consumption magnetic materials. For example, CN202111420511.5 of DMEGC announced a wide-temperature, low-loss, high-strength MnZn power ferrite and its preparation method and application. Under the conditions of 100kHz and 200mT, the power consumption of this material at 25℃ is ≤350mW / cm 3 , 120℃ power consumption ≤350mW / cm 3 ; Under the conditions of 1194A / m and 50Hz, the saturation flux density at 25℃ is ≥535mT. This material has excellent loss and saturation flux density characteristics at 25℃ to 120℃; Shanghai Baosteel Magnetics Co., Ltd.'s CN202310829822.X patent document discloses a wide temperature range of 25-140℃ low-loss soft magnetic manganese-zinc ferrite material and its preparation method and application. Under the conditions of 100kHz and 200mT, the power consumption at 25℃ is ≤350mW / cm 3 , 120℃ power consumption ≤350mW / cm 3 Both materials can meet the application range of temperature from 25℃ to 140℃ and have the characteristics of low loss, but their actual loss is >300mW / cm 3 However, switching power supplies such as servers and consumer electronics, where the load factor changes frequently, require lower energy consumption, and the above existing technologies cannot meet this demand. Since the operating temperature of the device is in the range of 25℃-80℃ most of the time when it is not fully loaded and the total power is less than 100W, it is necessary to further reduce the power loss caused by the device in the range of 25℃-80℃.

[0003] Therefore, how to provide a wide temperature range and ultra-low power consumption magnetic material with low power loss within 25°C-80°C is a technical problem that technical personnel in this field need to solve urgently. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a wide-temperature ultra-low power consumption magnetic material and a preparation method and application thereof.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a wide-temperature ultra-low power consumption magnetic material, wherein the wide-temperature ultra-low power consumption magnetic material comprises a main component and an auxiliary component;

[0007] Based on a molar fraction of 100%, the main components include 52.18-52.48 mol% Fe2O3, 10.5-10.7 mol% ZnO, and the remainder is MnO;

[0008] The auxiliary components include CaCO3, Nb2O5, Co2O3, Ta2O5 and SiO2;

[0009] Calculated by the weight of the main components, the addition amounts of the auxiliary components are respectively CaCO3 200-400ppm, Ta2O5 50-200ppm, Nb2O5 200-300ppm, Co2O3 3500-4500ppm, SiO2 20-100ppm;

[0010] The method for preparing the wide temperature and ultra-low power consumption magnetic material comprises the following steps:

[0011] The main material is mixed and ball-milled and then pre-sintered, and then the pre-sintered material is mixed with the auxiliary component and ball-milled continuously, and then spray-dried to obtain a powder, and then pressed into a mold and sintered to obtain the wide-temperature ultra-low power consumption magnetic material;

[0012] The sintering is specifically as follows: a heating stage: heating from 25°C to 1280°C in an air atmosphere for 6 hours;

[0013] Insulation stage: Insulation temperature is 1280℃, oxygen content is 3.2%, insulation time is 6h;

[0014] Cooling stage: cooling from 1280°C to 25°C at a cooling rate of 3°C / min under a balanced atmosphere.

[0015] The equilibrium atmosphere follows the Morineav formula logO2% = ab / T;

[0016] a, b are empirical constants, and T is the sintering Kelvin temperature.

[0017] Preferably, the pre-burning temperature is 900-920° C. and the time is 40-50 min.

[0018] Beneficial effects: The auxiliary components introduced in the present invention can enter the interior of the grains and the grain boundaries respectively, which can promote solid-phase reaction, reduce the sintering temperature, and control the growth of grains within a certain size range (the internal grain size is about 10μm or more, and the external grain size is less than 10μm). Among them, CaCO3 and SiO2 form high-resistivity CaSiO3, which is enriched at the grain boundaries, and can significantly increase the resistivity of the magnetic core, thereby reducing the loss factor. Ta in Ta2O5 is a high-valent ion. When it enters the interior of the crystal, it combines with Co2O3 to make Fe 3+ Convert to Fe 2+The appropriate addition amount of Ta2O5 and Co2O3 can make the magnetic anisotropy constant K1=0 move to low temperature, and multiple points of K1=0 appear, reducing the loss factor in the low temperature zone.

[0019] In addition, the present invention can obtain ultra-low power consumption magnetic materials by adopting a ZnO formula with more than 10% mol and a low temperature sintering process relative to the prior art to reduce the grain size. 2+ The content (controlling the bottom point of material power consumption) determines the oxidation degree and the oxygen content at each temperature point, draws the basic temperature curve and the equilibrium atmosphere curve, and the highest temperature insulation section is sintered at no more than 1280℃, which is much lower than the sintering temperature of other conventional wide-temperature and low-loss ferrite materials.

[0020] Preferably, the spinel synthesis degree of the pre-sintered material is 30-40%.

[0021] Preferably, the pressing molding is to mix the obtained powder with 2‰ zinc stearate and then press the mixture to obtain a powder with a density of 3g / cm 3 of the green body.

[0022] Preferably, the average particle size of the slurry obtained after ball milling is less than 1.2 μm.

[0023] Preferably, the average particle size of the slurry obtained after the continued ball milling is 1.0-1.1 μm.

[0024] A method for preparing a wide-temperature ultra-low power consumption magnetic material obtains a wide-temperature ultra-low power consumption magnetic material.

[0025] Application of a wide-temperature ultra-low power consumption magnetic material in a switching power supply.

[0026] The wide-temperature ultra-low power consumption magnetic material provided by the present invention can effectively reduce the energy consumption at light load or half load and improve efficiency.

[0027] Compared with the prior art, the present invention has the following advantages and technical effects:

[0028] The wide temperature and ultra-low power consumption magnetic material obtained by the present invention is a new material mainly developed for switching power supplies. The magnetic core prepared by the material is particularly suitable for power converters in switching power supplies, and can achieve optimal efficiency even when not fully loaded. This material has an alternating load factor, which is a unique advantage, especially when the power supply is not fully loaded. In the above situation, heat loss can be reduced, thereby avoiding unnecessary energy consumption. This material is typically used in power supplies, which are usually used to power servers whose load factors change frequently. The magnetic material obtained by the present invention has lower wide temperature power consumption, wide temperature and ultra-low power consumption, and an application temperature range of 0°C to 120°C. It also has very high saturation flux density and magnetic permeability, especially in the range of 25°C-80°C, and the power loss can be as low as 200mW / cm 3 It is very suitable for the production of power converters in servers and consumer electronics where the load factor changes frequently, and is the current core material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 It is a comparison diagram of power loss between Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0033] The embodiment of the present invention discloses a method for preparing a wide-temperature ultra-low power consumption magnetic material, wherein the wide-temperature ultra-low power consumption magnetic material comprises a main component and an auxiliary component;

[0034] Based on a molar fraction of 100%, the main components include 52.18-52.48 mol% Fe2O3, 10.5-10.7 mol% ZnO, and the remainder is MnO;

[0035] The auxiliary components include CaCO3, Nb2O5, Co2O3, Ta2O5 and SiO2;

[0036] Calculated by the weight of the main components, the addition amounts of the auxiliary components are respectively CaCO3 200-400ppm, Ta2O5 50-200ppm, Nb2O5 200-300ppm, Co2O3 3500-4500ppm, SiO2 20-100ppm;

[0037] The method for preparing the wide temperature and ultra-low power consumption magnetic material comprises the following steps:

[0038] The main material is mixed and ball-milled and then pre-sintered, and then the pre-sintered material is mixed with the auxiliary component and ball-milled continuously, and then spray-dried to obtain a powder, and then pressed into a mold and sintered to obtain the wide-temperature ultra-low power consumption magnetic material;

[0039] The sintering is specifically as follows: a heating stage: heating from 25°C to 1280°C in an air atmosphere for 6 hours;

[0040] Insulation stage: Insulation temperature is 1280℃, oxygen content is 3.2%, insulation time is 6h;

[0041] Cooling stage: cooling from 1280°C to 25°C at a cooling rate of 3°C / min under a balanced atmosphere.

[0042] The equilibrium atmosphere follows the Morineav formula logO2% = ab / T;

[0043] a, b are empirical constants, and T is the sintering Kelvin temperature.

[0044] Preferably, the pre-burning temperature is 900-920° C. and the time is 40-50 min.

[0045] In a preferred embodiment, the pre-burning temperature is 900-920° C. and the time is 40-50 min.

[0046] In a preferred embodiment, the spinel synthesis degree of the pre-sintered material is 30-40%.

[0047] In a preferred embodiment, the pressing molding is to mix the obtained powder with 2‰ zinc stearate and then press the mixture to obtain a powder with a density of 3g / cm 3 of the green body.

[0048] In a preferred embodiment, the average particle size of the slurry obtained after ball milling is less than 1.2 μm.

[0049] In a preferred embodiment, the average particle size of the slurry obtained after the continued ball milling is 1.0-1.1 μm.

[0050] The embodiment of the present invention also discloses an application of a wide temperature range, low power consumption and high Bs manganese-zinc ferrite material in a switching power supply.

[0051] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0052] The room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.

[0053] The equilibrium atmosphere described in the embodiment of the present invention follows the Morin Liu formula logO2%=ab / T;

[0054] a, b are empirical constants, and T is the sintering Kelvin temperature.

[0055] Example 1

[0056] A method for preparing a wide-temperature ultra-low power consumption magnetic material comprises the following steps:

[0057] (1) 52.18 mol% of Fe2O3, 37.32 mol% of MnO and 10.5 mol% of ZnO were mixed and ball-milled, wherein the material-water ratio was 1:1.1, the material-ball ratio was 1:3 (the ball was a steel ball with a diameter of ф=2.96 mm), the ball-milling time was 30 min, and the average particle size of the slurry was below 1.2 μm; then the obtained powder was pre-calcined for 0.7 h in a natural gas 500 type rotary kiln at 910° C. in an air atmosphere, during which the feed rate was 2-3 kg / hour and the rotation speed was 2 N / minute, to obtain a pre-calcined material with a spinel synthesis degree of 30-40%;

[0058] (2) mixing the pre-sintered material obtained in step (1) with auxiliary components to obtain a mixed powder, then ball-milling the mixed powder to obtain a slurry with an average particle size of 1.00-1.10 μm, adding a PVA solution (concentration of 8%) of 10% by weight of the mixed powder to the slurry, stirring for 120 minutes, and spray drying to obtain a powder;

[0059] Among them, the auxiliary material components are CaCO3, Ta2O5, Nb2O5, Co2O3, and SiO2, and the content of each substance calculated by the weight of the main components is: CaCO3 300ppm, Nb2O5 300 ppm, Co2O3 4500 ppm, Ta2O5 120ppm, and SiO2 60ppm.

[0060] During the ball milling process, the material-water ratio was 1:1, the material-ball ratio was 1:5 (the ball was a steel ball of ф=3mm), and the ball milling time was 70min;

[0061] (3) The powder obtained in step (2) was mixed with 2‰ of zinc stearate and pressed into a mold to obtain a density of 3g / cm 3 The standard green body is then sintered at a specific curve and cooled to obtain a wide temperature and ultra-low power consumption magnetic material.

[0062] Among them, the sintering curve is as follows: heating stage: from 25°C to 1280°C, heating for 6h in air atmosphere;

[0063] Insulation stage: Insulation temperature is 1280℃, oxygen content is 3.2%, insulation time is 6h;

[0064] Cooling stage: cooling from 1280°C to 25°C at a cooling rate of 3°C / min under a balanced atmosphere.

[0065] Example 2

[0066] A method for preparing a wide-temperature ultra-low power consumption magnetic material, which is different from that of Example 1 in that, in step (1), 52.38 mol% of Fe2O3, 36.92 mol% of MnO and 10.7 mol% of ZnO are mixed and then ball-milled;

[0067] In step (2), the contents of the auxiliary components calculated based on the weight of the main components are: CaCO3 200ppm, Nb2O5 300ppm, Co2O3 4500ppm, Ta2O5 60ppm, SiO2 80ppm.

[0068] Comparative Example 1

[0069] A method for preparing a wide-temperature ultra-low power consumption magnetic material, which is different from that of Example 1 in that, in step (1), 52.48 mol% of Fe2O3, 36.67 mol% of MnO and 10.85 mol% of ZnO are mixed and then ball-milled;

[0070] In step (2), the contents of the auxiliary components calculated based on the weight of the main components are: CaCO3 200ppm, Nb2O5 300ppm, Co2O3 4000ppm.

[0071] Comparative Example 2

[0072] A method for preparing a magnetic material, which is different from Example 1 in that Co2O3 is omitted, and the remaining steps are the same as those of the example.

[0073] Comparative Example 3

[0074] A method for preparing a magnetic material, which is different from Example 1 in that the sintering curve in step (3) is:

[0075] Heating stage: from 25℃ to 1300℃ in air atmosphere for 6h;

[0076] Insulation stage: Insulation temperature is 1300℃, oxygen content is 3.2%, insulation time is 6h;

[0077] Cooling stage: cooling from 1300°C to 25°C at a cooling rate of 1.5°C / min under a balanced atmosphere.

[0078] Comparative Example 4

[0079] A method for preparing a magnetic material, which is different from that of Example 1 in that, in step (1), 53.5 mol% of Fe2O3, 37.3 mol% of MnO and 9.2 mol% of ZnO are mixed and then ball-milled;

[0080] Technical effects:

[0081] The magnetic materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and the magnetic permeability was measured using an E4980A LCR bridge, and the power consumption was tested using a SY8218 BH loop meter. The results are shown in Table 1:

[0082] Table 1

[0083]

[0084] It can be seen that the power consumption of the material obtained in the present invention is ≤200mW / cm at 25°C under the conditions of 100kHz and 200mT. 3 , 120℃ power consumption ≤300mW / cm 3 , the initial magnetic permeability is above 3500.

[0085] Figure 1 This is a power loss comparison diagram of Example 1 of the present invention and Comparative Example 1. It can be seen from the figure that although the power consumption of the embodiment presents a positive temperature coefficient, the power consumption in the range of 20-80°C is much lower than that of the comparative example.

[0086] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a wide temperature and ultra-low power consumption magnetic material, characterized in that: The wide temperature and ultra-low power consumption magnetic material comprises a main component and an auxiliary component; Based on a molar fraction of 100%, the main components include 52.18-52.48 mol% Fe2O3, 10.5-10.7 mol% ZnO, and the remainder is MnO; The auxiliary components include CaCO3, Nb2O5, Co2O3, Ta2O5 and SiO2; Calculated by the weight of the main components, the addition amounts of the auxiliary components are respectively CaCO3 200-400ppm, Ta2O5 50-200ppm, Nb2O5 200-300ppm, Co2O3 3500-4500ppm, SiO2 20-100ppm; The method for preparing the wide temperature and ultra-low power consumption magnetic material comprises the following steps: The main material is mixed and ball-milled and then pre-sintered, and then the pre-sintered material is mixed with the auxiliary component and ball-milled continuously, and then spray-dried to obtain a powder, and then pressed into a mold and sintered to obtain the wide-temperature ultra-low power consumption magnetic material; The sintering is specifically as follows: a heating stage: heating from 25°C to 1280°C in an air atmosphere for 6 hours; Insulation stage: Insulation temperature is 1280℃, oxygen content is 3.2%, insulation time is 6h; Cooling stage: cooling from 1280°C to 25°C at a cooling rate of 3°C / min under a balanced atmosphere.

2. The method for preparing a wide temperature and ultra-low power consumption magnetic material according to claim 1, characterized in that: The pre-burning temperature is 900-920° C. and the pre-burning time is 40-50 minutes.

3. The method for preparing a wide temperature and ultra-low power consumption magnetic material according to claim 1, characterized in that: The spinel synthesis degree of the pre-sintered material is 30-40%.

4. The method for preparing a wide temperature and ultra-low power consumption magnetic material according to claim 1, characterized in that: The pressing molding is to mix the obtained powder with 2‰ zinc stearate and then press the mixture to obtain a density of 3g / cm 3 of the green body.

5. The method for preparing a wide temperature and ultra-low power consumption magnetic material according to claim 1, characterized in that: The average particle size of the slurry obtained after the ball milling is less than 1.2 μm.

6. The method for preparing a wide temperature and ultra-low power consumption magnetic material according to claim 1, characterized in that: The average particle size of the slurry obtained after the continuous ball milling is 1.0-1.1 μm.

7. A wide temperature and ultra-low power consumption magnetic material prepared according to the method for preparing a wide temperature and ultra-low power consumption magnetic material according to any one of claims 1 to 6.

8. Application of the wide temperature and ultra-low power consumption magnetic material as claimed in claim 7 in a switching power supply.

Citation Information

Patent Citations

  • MnZn ferrite material and method of manufacturing the magnetic core

    CN101183585A

  • Wide-temperature low-loss high-strength MnZn power ferrite, and preparation method and application thereof

    CN113956032A

  • PROCESS FOR PREPARING LOW-LOSS MnZn FERRITE AND CALCINED POWDER

    JP2004067444A

  • Wide-temperature low-loss mnzn ferrite material, and preparation method therefor

    WO2022000663A1